Legal Responsibility of Business Actors to Consumers in Subsidized Houses Related to the Quality of Livable Houses - Aryandi, Laskar Surya; Pratama , Ferdi Ardiansyah; Athallah , Dafi Najmi; Hidayat , Dudung; Handiriono , Raden (Journal of Legal and Cultural Analytics, 2025)
Housing is one of the basic needs that every individual in society must meet. To create equitable access to decent housing, the government has launched a housing subsidy program aimed at low-income communities. Although this program has a positive purpose, in practice, there are still various problems, especially related to violations of legal standards in the agreement to sell subsidized houses. One of the crucial issues that arises is related to the quality of houses that do not meet the livable criteria and the lack of legal protection for consumers or subsidized housing buyers. The main purpose of this study is to analyze the legal responsibilities of business owners in the agreement to sell subsidized houses in order to identify violations of legal norms that occur in the transaction. This study uses normative juridical data, such as legal regulations, books, scientific journals, and other relevant topics related to research. The results of this study show that the Consumer Protection Law Number 8 of 1999 provides legal protection to consumers for the actions of business owners in selling houses by affirming the responsibility of business owners to ensure legal certainty over consumer rights in providing a decent home. Following the specific agreements conveyed, fairness and balance in the relationship between business and consumers, especially in implementing the sales and marketing of fair, efficient, and cheap goods and services, should be realized through consumer protection laws or legal channels if consumer rights are violated.